Education and Health: Long-run Effects of Peers, Tracking and Years - Martin Fischer; Ulf-Göram Gerdtham,; Gawain Heckley; Martin Karlsson; Gustav Kjellsson; Therese Nilsson (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2019)
We investigate two parallel school reforms in Sweden to assess the long-run health effects of education. One reform only increased years of schooling, while the other increased years of schooling but also removed tracking leading to a more mixed socioeconomic peer group. By differencing the effects of the parallel reforms, we can separate the effect of de-tracking and peers from that of more schooling. We find that the pure years of schooling reform reduced mortality and improved current health. Differencing the effects of the reforms shows significant differences in the estimated impacts, suggesting that de-tracking and subsequent peer effects resulted in worse health.
Keywords: I12; I18; I26; 330; Health returns to education; school tracking; peer effects